2018
DOI: 10.1002/iub.1895
|View full text |Cite
|
Sign up to set email alerts
|

P53‐dependent induction of ferroptosis is required for artemether to alleviate carbon tetrachloride‐induced liver fibrosis and hepatic stellate cell activation

Abstract: Ferroptosis is recently reported as a new mode of regulated cell death. Its essential characteristics are disturbed redox homeostasis, overloaded iron, and increased lipid peroxidation. However, the role of ferroptosis in liver fibrosis remains poorly understood. In this study, we attempted to investigate the effect of artemether (ART) on ferroptosis in hepatic fibrosis and to further clarify the possible mechanisms. Our data showed that ART treatment markedly attenuated liver injury and reduced fibrotic scar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 135 publications
(100 citation statements)
references
References 48 publications
3
97
0
Order By: Relevance
“…Ferroptosis is a lipid-and iron-dependent form of cell death that is different from cell apoptosis, pyroptosis and autophagy. Recently, studies found that ferroptosis biomarkers (ROS, MDA and GPX4) have been detected in the tissues of fibrosis-related diseases [52][53][54]. In the present study, we found that the expression of ROS and MDA were upregulated in HFL1 cells treated with TGF-β1, but GPX4 expression was decreased.…”
Section: Agingsupporting
confidence: 61%
“…Ferroptosis is a lipid-and iron-dependent form of cell death that is different from cell apoptosis, pyroptosis and autophagy. Recently, studies found that ferroptosis biomarkers (ROS, MDA and GPX4) have been detected in the tissues of fibrosis-related diseases [52][53][54]. In the present study, we found that the expression of ROS and MDA were upregulated in HFL1 cells treated with TGF-β1, but GPX4 expression was decreased.…”
Section: Agingsupporting
confidence: 61%
“…Therefore, effective suppression of inflammation and improvement of inflammatory microenvironment are critical to control the progression of liver fibrosis. Currently, anti‐inflammatory drugs have been widely used to control liver inflammation in clinical, of which, remarkable achievements has been made using natural products to prevention and treatment of liver fibrosis in experimental and clinical research . Tripterygium wilfordii Hook F (TwHF), a Chinese medicinal plant, shows potent anti‐inflammatory effect, especially in rheumatoid arthritis (RA).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ferroptosis is closely related to the pathophysiological processes of more and more diseases. For example, ART treatment can significantly reduce the degree of liver injury and inhibit the formation of fibrotic scars in mice with liver fibrosis, in which the morphological characteristics of ferroptosis appear in hepatocytes 82 . Other studies have found that islets are indeed susceptible to ferroptosis in vitro.…”
Section: Ferroptosis and Other Diseasesmentioning
confidence: 99%